Hand injuries in low- and middle-income countries: systematic review of existing literature and call for greater attention. (September 2018) - Siotos, C.; Ibrahim, Z.; Bai, J.; Payne, R.M.; Seal, S.M.; Lifchez, S.D.; Hyder, A.A.
Abstract: Objectives: Hand injuries result in major healthcare costs from lack of productivity and disability. With rapid industrialization, the incidence of hand injuries is expected to rise in low- and middle-income countries (LMICs). However, estimates of burden and validated outcome tools are needed for effective resource allocation in the management of these injuries. Study design: We conducted a systematic review to evaluate the burden of hand injuries in LMICs according to Preferred Reporting Items for Systematic Review and Meta-Analyses guidelines. Methods: We searched PubMed, Scopus, Embase, Cochrane Library, PAIS International, African Index Medicus, Global Health, IMMEMR, IMSEAR, Wholis and Bdenf, Lilacs, Scielo, WPRIM, and WHO International Clinical Trials Registry Platform to detect eligible articles with no restrictions on length of follow-up, type of hand injury, or date. Results: We included 17 articles after screening 933 eligible articles based on title, abstract, and full-text screening. There was significant heterogeneity and low quality of evidence. All included articles suggest that hand injuries were associated with work limitations for the majority of patients, and residual pain can further limit their activities. Direct and indirect costs related to treatment account for a major healthcare burden with limited evidence on estimates of long-term cost from disability. Conclusions: The present systematic review highlights the paucity of high-quality data on the epidemiology, management, and burden of hand injuries in LMICs. The data are heterogeneous, and comprehensive metrics are lacking. Because hand injuries can account for a significant proportion of injury-related disability, reducing the overall burden of hand injuries is of utmost importance. Highlights: We included 17 articles after screening 933 eligible articles. Hand injuries were associated with work limitation. Direct and indirect costs related to treatments account for a major healthcare burden. Limited evidence exist on estimates of long-term cost from disability. Disparities exist in the hand injury research in low- and middle-income countries.